SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN RUMAH TINGGAL MENGGUNAKAN METODE TOPSIS - Wibowo, Mohamad Hegar Sukmana; Ayubi, Muhammad Din Al; Albedri, Muhammad; Fermana, Yudi; Anshor, Abdul Halim (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Choosing a residential property is a complex decision involving multiple criteria such as price, location, facilities, and risks. To assist potential buyers in making more objective decisions, this research developed a Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. TOPSIS is employed to process various criteria and rank housing alternatives based on their proximity to the ideal solution. The results demonstrate that this system effectively provides recommendations that align with user preferences, with location and price being the dominant factors. The implementation of TOPSIS is expected to improve user satisfaction and reduce dissatisfaction risks in residential property selection.